A homeopatia como indutora de resistência do feijoeiro à herbivoria de insetos em sistemas agroecológicos - Deboni, Tarita Cira (2019)
Homeopathy has been showing results in plant metabolism, promoting its natural defenses, which can be measured through biochemical and physiological analyses. However, little is known about the role of homeopathic preparations in the plant defense system against insect herbivory, and whether they can act as resistance inducers promoting plant self-regulation. The objective of this study was to evaluate if homeopathic preparations act on resistance induction in common bean against insect herbivory in agroecological transition systems. The first experiment was a screening, in which the following homeopathic preparations were tested: Arsenicum album, Staphisagria, Silicea terra and Sulphur, in the potencies 6CH, 12CH and 18CH, compared to the controls. For the second experiment, only Arsenicum album 6CH, Silicea terra 6CH, Staphisagria 12CH and Sulphur 6CH were selected. Both experiments were conducted in a completely randomized design, with the application of the treatments at 1% in distilled water and compared to the controls. In the second experiment the common bean was grown in two subsequent generations: the first was the parental one and the second was the progeny and, in this case, there was a stress caused by the herbivory of the Helicoverpa armigera (Lepidoptera: Noctuidae) caterpillar. Protein concentration and activity of guaiacol peroxidase (POD) and ascorbate peroxidase (APX) enzymes in bean leaves and roots were determined. Differences among treatments and controls from both experiments were estimated by Glass’s Delta effect size analysis. The third experiment was conducted in the field, in the 2019 crop, in a double factorial design with split plot scheme. Arsenicum album 6CH, Silicea terra 6CH and the control with distilled water were arranged in the plot and, in the subplot, it was allocated the presence or absence of a protective screen. The variables analyzed were protein concentration, phenylalanine ammonia lyase activity (FAL), lipid peroxidation (MDA), gas exchange, chlorophyll content, yield components, and protein and total nitrogen in the grains. In the laboratory, three trials were performed with the H. armigera caterpillar, one of them with free choice, evaluating the antixenosis effect and the other without chance of choice, assessing the antibiosis effect. Data from these last tests were subjected to analysis of variance and the means were compared by Tukey test (p<0.05). The homeopathic preparations of Arsenicum album, Silicea terra, Staphisagria and Sulphur caused changes in protein concentration and in the activity of peroxidases, APX and POD on bean plants cultivated in greenhouse. These changes showed transgenerational effect when the plants were exposed to herbivory damage caused by H. armigera caterpillar, indicating the potential resistance induction of these homeopathies. The common bean treated with homeopathic preparations of Arsenicum album 6CH and Silicea terra 6CH caused antixenosis and antibiosis responses in H. armigera caterpillars. These results demonstrate that homeopathy can induce plant defense systems, facilitating the agroecological transition processes.